PEMANFAATAN AKUN-AKUN TERKAIT SOSIOLOGI TERHADAP PENGGUNA INSTAGRAM MAHASISWA SOSIOLOGI FISIP UNRI - Rajvi, Raynal; Hidir, Achmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Utilization of Sociology Accounts on Instagram Users of Fisip Unri Sociology Students. This research was especially conducted at The Sociology Student of Fisip University of Riau in the years 2017, 2018 and 2019. The purpose of this study is to measure and find out how sociology students utilize sociology accounts found on instagram as a means of supporting science, insight enhancers and lecture referrals. In this research method, it was conducted using a quantitative approach with the form of Parametric Inference, which is normal distributed data with a sample number of more than a hundred respondents. The determination of the subjects in this study used simple random sampling technique as many as 180 people from a population of 340 people. The theory used in this study is the Hyperreality Theory of Symbolic Marks and Values by Jean Baudrillard. The result of the research was known that in the utilization of sociological accounts, respondents had a moderate category utilization rate or with a percentage of 65.6 %. Utilization rates are distinguished into the first two forms, utilization rates based on gender. Second, the utilization rate is based on the year of the force. The rate of utilization based on gender found that women are more consigned to utilizing sociological accounts. Then by force year, the year of 2019 contributes more in utilizing sociological accounts.  Keywords : Utilization, Sociology Accounts, Instagram, Hiperreality, Mark Value and Symbolic Value.